The Role of Soil Solarization in India: How an Unnoticed Practice Could Support Pest Control - Gill, Harsimran K.; Aujla, Iqbal S.; De Bellis, Luigi; Luvisi, Andrea (Frontiers in Plant Science, 2017)
Plant protection represents one of the strategies to fill the yield gap and to achieve food security, a key topic for India development. Analysis of climate risks for crops indicates that South Asia is one of the regions most exposed to the adverse impact on many plants that are relevant to inhabitants exposed to food safety risks. Furthermore, accumulation of pesticide residues in the aquatic and other ecosystems is becoming a significant threat in India. These perspectives require to develop programs of crop protection that can be feasible according to Indian rural development and pollution policy. Here we review the research works done on soil solarization in India. Soil solarization (also called plasticulture) is an eco-friendly soil disinfestations method for managing soil-borne plant pathogens. This is the process of trapping solar energy by moist soil covered with transparent polyethylene films and chemistry, biology and physical properties of soil are involved in pest control. So far, this technique is applied in more than 50 countries, mostly in hot and humid regions. India has 29 states and these states fall under five climatic zones, from humid to arid ones. We report pest management application in different climatic zones and their effects on production, weeds, nematodes and pathogenic microorganisms. The analysis of soil temperatures and crop protection results indicate as environmental requirement for soil solarization fits in most of Indian rural areas. Soil solarization is compatible with future Indian scenarios and may support Indian national food security programs.